Exploring the complexity of Drosophila suzukii control: morphological variations and toxicological responses - Santos, Vinícius Fonsêca dos (2024)
The present master’s dissertation focuses on the study of Drosophila suzukii, a non- native species that has established itself in Brazil and is expanding its presence in various regions of the country. The remarkable capacity for adaptation and geograph- ical expansion of this species is attributed to its plasticity. The work arises with the purpose of understanding the plasticity of D. suzukii and exploring alternatives for its control. Two fundamental questions guide this research: What are the main trends and perspectives regarding the use of essential oils in the control of D. suzukii and their impact on non-target organisms? and does the external morphology of D. suzukii populations vary depending on the region where they are found? To address these questions, the thesis is divided into two distinct chapters. In the ﬁrst, we conducted an exhaustive systematic review highlighting the main trends and perspectives regarding the use of essential oils in the control of D. suzukii. There is a lack of attention to the effect of these substances on non-target organisms, as well as a scarcity of studies on their modes of action and effectiveness under ﬁeld conditions. The second chapter delves into the study of sexual dimorphism between males and females of D. suzukii, as well as the morphological variations of wings collected in Minas Gerais and Rio Grande do Sul states. The results indicate that sexual dimorphism is primarily marked by size, with female wings being larger than male wings. However, population differences are more deﬁned by shape than size. Additionally, the potential of a biorational tool for D. suzukii control is explored, highlighting the insecticidal activity of Ruta chalepensis essential oil against both populations of D. suzukii. Although the results did not show signiﬁcant variation in toxicological response between populations, they offer valuable contributions to understanding the plasticity of D. suzukii and to the development of more effective and sustainable control strategies in agriculture. Keywords: Essential oils. Plasticity. Toxicology. Spotted-wing Drosophila.